Reparo ósseo dedefeitos de tamanho crítico tratados com aspirado de medula óssea associado ou não a terapia com laser em baixa intensidade: estudo imunoistoquímico em calvárias de ratos - Santinoni, Carolina dos Santos [UNESP] (2015)
This immunohistochemical study evaluated the influence of bone marrow aspirate (BMA) combined or not with low-level laser therapy (LLLT) on bone healing in surgically created critical-size defects (CSDs) in rat calvaria. 64 rats were randomly divided into 4 groups: C (control), BMA, LLLT and BMA/LLLT. A 5 mm diameter CSD was created in the calvarium of each animal. In Group C, the defect was filled by blood clot only. In Group BMA, the defect was filled with BMA. In groups LLLT and BMA/LLLT, the defect received laser irradiation (InGaAlP laser), was filled with blood clot or BMA respectively, and irradiated again. Animals were euthanized at either 15 or 30 days postoperative. Vascular endothelial growth factor (VEGF), proliferating cell nuclear antigen (PCNA), runt-related transcription factor-2 (Runx2), bone morphogenetic protein-2 (BMP-2), osteocalcin (OCN) and osteopontin (OPN) immunohistochemical staining were performed. A semi-quantitative method was used to evaluate VEGF immunolabeling. PCNA-positive, Runx2-positive, BMP-2-positive, OPN-positive and OCN-positive cells were quantified. Data were statistically analyzed. At 15 days postoperative, Group LLLT presented a significantly higher number of OPN-positive and OCN-positive cells than Group C; Group BMA presented a significantly higher number of PCNA-positive, Runx2-positive, BMP-2-positive and OPN-positive cells than groups C and LLLT, and a significantly higher number of OCN-positive cells than control; Group BMA/LLLT presented significantly higher VEGF immunolabeling and number of Runx2-positive, OPN-positive and OCN-positive cells than Group C. At 30 days postoperative, Group LLLT presented significantly higher VEGF immunolabeling and number of OPN-positive and OCN-positive cells than Group C; Group BMA presented a higher number of Runx2-positive, BMP-2-positive and OCN-positive cells than Group C; Group BMA/LLLT presented...